The lynching of William Parker: The criminal justice system at work in 19th century North Carolina - Campbell, James M. (American journal of criminal justice, 1982)
An examination of primary sources of a nineteenth century lynching reveals that in some parts of the south the criminal justice system often involved non-official citizen involvement rather than official agencies of law enforcement in the investigation of crimes.